WORK FROM HOME, DISIPLIN KERJA, DAN PRODUKTIVITAS KARYAWAN: SEBUAH SYSTEMATIC LITERATURE REVIEW - Ades Asike; A. Fitri Sugi Angka; Darmawansah Darmawansah (Universitas Ichsan Sidenreng Rappang, 2026)
The development of flexible work arrangements in the post-COVID-19 era has significantly increased the implementation of Work From Home (WFH) practices across various organizations. This transformation has raised concerns regarding the factors influencing employee productivity, particularly work discipline as a behavioral control mechanism in remote working environments. Therefore, a systematic review is needed to integrate fragmented research findings and provide a more comprehensive understanding of the relationship between WFH, work discipline, and employee productivity. This study aims to identify research trends, analyze the theoretical and methodological approaches employed in previous studies, synthesize the relationships among variables, and identify existing research gaps. The study adopted a Systematic Literature Review (SLR) approach following the PRISMA 2020 guidelines. Literature searches were conducted through Scopus, Web of Science, ScienceDirect, Emerald Insight, SpringerLink, ProQuest, and Google Scholar databases covering the period from 2020 to 2025. Following the identification, screening, and eligibility assessment processes, 35 articles met the inclusion criteria and were analyzed using thematic analysis and narrative synthesis. The review findings indicate that WFH generally contributes positively to employee productivity by enhancing work flexibility and work-life balance. However, its effectiveness is strongly influenced by work discipline, organizational support, and the utilization of digital technology. Furthermore, inconsistencies were identified across studies due to differences in organizational contexts, job characteristics, and research designs. This study concludes that work discipline is a key determinant of successful WFH implementation and proposes an integrated conceptual framework that can serve as a foundation for future research, human resource management practices, and flexible work policy development.